Methods for producing carbon from lignin
The method of producing carbon from lignin with low metal content addresses the issue of high metal interference in energy storage applications, resulting in improved electrochemical properties and long-term performance for carbon materials.
Patent Information
- Application Number
- JP2024558343
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-04
- Filing Date
- 2023-04-03
- Publication Date
- 2025-04-15
AI Technical Summary
Existing methods for producing carbon from lignin often result in high metal content, which interferes with the electrochemical properties and long-term cycling performance of carbon-enriched materials used in energy storage applications.
A method involving the preparation of lignin with a total metal content of less than 200 ppm, followed by heat treatment at temperatures ranging from 300°C to 1500°C to produce carbon with low metal content, suitable for energy storage applications.
The method effectively reduces the metal content in carbon materials, enhancing their electrochemical properties and long-term cycling performance, making them suitable for use in energy storage devices such as lithium-ion batteries.
Smart Images

Figure 2025511319000001 
Figure 2025511319000002 
Figure 2025511319000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing carbon from lignin having a total metal content of less than 200 ppm. The present invention further relates to carbon obtained from lignin having a total metal content of less than 800 ppm, the low metal content of which makes the carbon suitable for use in energy storage applications. [Background technology]
[0002] Carbon enriched materials can be used for a variety of end uses, such as biochar, activated carbon, and energy storage materials. Today, carbon enriched materials are mostly produced from fossil fuel-based precursors.
[0003] As an alternative to fossil fuel-based carbon-containing materials, the use of lignin would be a preferred option. Lignin (an aromatic polymer) is the main component in wood, for example, and is the most abundant source of carbon on Earth after cellulose. In recent years, technologies have been developed and commercialized to extract lignin from the pulp manufacturing process in a specific form in a high-purity solid form, which has attracted considerable attention as a potential renewable alternative to the main aromatic chemical precursors currently supplied by the petrochemical industry.
[0004] Carbon-rich materials are also used as anodes in secondary batteries (e.g., lithium-ion batteries). Graphite (natural or synthetic) is commonly utilized today as the anode material in most lithium-ion batteries. Alternatives to graphite include amorphous carbon materials, such as hard carbon (amorphous carbon that cannot be graphitized) and soft carbon (amorphous carbon that can be graphitized), which lack the long-range order of graphite. Amorphous carbon can be used as the sole active material or in mixtures with graphite (and / or other active materials) and can be derived from lignin. Lignin-derived amorphous carbon is typically non-graphitizable, i.e., hard carbon.
[0005] Today, the most important commercially available source of lignin is Kraft lignin. It is obtained from hardwoods or softwoods by the Kraft process. Lignin can be separated from alkaline black liquor, for example, by membrane filtration or ultrafiltration. LignoBoost is one common separation process, described for example in WO2006031175 A1. In this process, lignin is precipitated from alkaline black liquor by lowering the pH level (usually by adding carbon dioxide) and then filtered off. The lignin filter cake is reslurried in acidic conditions (usually with sulfuric acid) and washed in a next step. The precipitated and washed lignin can be used as is or can be further dried.
[0006] Black liquor is a cost-effective source of lignin because it is readily available as a by-product from the Kraft process. However, black liquor contains a certain amount of metals (mostly from the wood and from the cooking chemicals used during the pulping process), and therefore the lignin precipitated from black liquor will also contain certain amounts of metals. Lignin generally contains relatively high levels of sodium and potassium, and will also contain small amounts of other metals (e.g. aluminum, calcium, iron, magnesium, and manganese). Lignin may also contain trace amounts of other metals.
[0007] Some metals, such as sodium and potassium, can be largely removed from the precipitated lignin by an acid wash step during the separation process, however, other metals, such as iron, are more difficult to remove from the precipitated lignin.
[0008] The requirements for the purity of carbon-rich materials used in applications such as energy storage applications are stringent. It is therefore important that the purity level of the lignin used to produce carbon intended for these applications is sufficiently high. In particular, the metal content of the lignin must be sufficiently low. Any metals present in the lignin will remain after carbonization and therefore will also be present in the carbon-rich material. Such metals may, for example, interfere with the function of the carbon-rich material (e.g., electrochemical properties and long-term cycling performance). In particular, transition metals (e.g., iron and manganese), when present in energy storage applications involving carbon-rich materials derived from lignin, have a negative impact on the long-term stability of the energy storage device. This is believed to be caused by the precipitation of transition metals during charging and discharging and by the decomposition of the electrolyte due to reactions catalyzed by transition metals.
[0009] In addition, metals present during the carbonization of lignin can catalyze processes that lead to structural modifications in the resulting carbon-rich material. Preserving carbon structure is particularly important when the carbon-rich material is intended for use in applications such as energy storage devices and capacitors, where carbon structure is crucial for the proper functioning of the devices.
[0010] Lignin can also be obtained by various fractionation methods (such as the organosolv process or hydrolyzed lignin), however the organosolv process is of less commercial interest for producing lignin than the kraft process.
[0011] Various attempts have been made to remove metals from lignin, but what these methods have in common is that they are fairly complicated, involving many additional processing steps, and / or the metal removal efficiency is not sufficiently efficient, the purity level is insufficient, and / or the washing times are long.
[0012] Korean Patent No. 101451299 (KR101451299 B1) discloses a method for obtaining lignin with a low ash content by repeatedly dissolving and precipitating lignin, however, many additional steps are required.
[0013] WO2020013752 A1 discloses a method for dissolving lignin in an acidic aqueous solution. A two-phase system is obtained by phase separation, where one phase is lignin-rich and the other phase is lignin-poor, and this other phase contains metal cations extracted from the lignin. However, many additional steps are required.
[0014] Thus, there is a need for improved methods for producing carbon with sufficiently low metal content so that the carbon is suitable for use in energy storage applications. Moreover, it is desirable that the methods be cost-effective and compatible with large-scale manufacturing.
[0015] Summary of the Invention It is an object of the present invention to provide an improved process for producing carbon from lignin, which eliminates or mitigates at least some of the disadvantages of the prior art processes.
[0016] It is a further object of the present invention to provide an improved process for producing carbon from lignin, which has a sufficiently low metal content to make it suitable for use in energy storage applications, such as for producing hard carbon active materials in the negative electrodes of secondary batteries (e.g. lithium ion batteries).
[0017] It is a further object of the present invention to provide a method for producing refined carbon from lignin that is amenable to large-scale production.
[0018] These and other objects are accomplished by the various aspects of the present invention, as will be appreciated by those skilled in the art upon access to the invention.
[0019] According to a first aspect, the present invention relates to a method for producing carbon, the method comprising the steps of: i) providing lignin having a total metals content of less than 200 ppm; ii) subjecting the lignin to a heat treatment at one or more temperatures in the range of 300° C. to 1500° C., the heat treatment being carried out for a total time of 30 minutes to 10 hours to obtain carbon; Includes.
[0020] The method according to the invention according to the first aspect is based on the surprising finding that carbon suitable for use in energy storage applications can be achieved by carbonizing lignin having a total metal content of less than 200 ppm. Due to the low metal content in the lignin, the carbon obtained from said lignin also has a low metal content. In particular, the resulting carbon has a low iron and / or manganese content.
[0021] Preferably, the lignin having a total metal content of less than 200 ppm is obtained by a process comprising the steps of: a) providing a solid lignin; b) providing an acidic aqueous solution having a pH below 6; c) soaking the lignin in an acidic aqueous solution for at least 15 minutes, the temperature of the acidic aqueous solution during soaking being in the range of 40° C. to 100° C. to remove metals from the lignin and transfer them to the acidic aqueous solution, thereby obtaining a purified lignin having a total metal content of less than 200 ppm; d) separating the resulting purified lignin from the acidic aqueous solution; and e) Optionally, washing the separated purified lignin Here the lignin remains in solid form during all steps of the process.
[0022] Surprisingly, it has been found that metals can be removed by immersing the lignin in an acidic aqueous solution for at least 15 minutes at temperatures ranging from 40° C. to 100° C. This allows for a rapid method for purifying lignin with few additional process steps, making the method compatible with large-scale production.
[0023] According to a second aspect, the present invention relates to carbon derived from lignin, the carbon having a total metal content of less than 400 ppm.
[0024] The carbon according to the second aspect can be preferably used in energy storage applications, such as the active material in the negative electrode of a secondary battery. The low metal content in the carbon leads to improved electrochemical properties, such as charge / discharge capacity and long-term cycle performance.
[0025] According to a third aspect, the invention relates to a negative electrode for a non-aqueous secondary battery comprising, as active material, a carbon obtainable by the method according to the first aspect.
[0026] According to a fourth aspect, the present invention relates to the use of carbon obtainable by the method according to the first aspect as active material in the negative electrode of a secondary battery, for example a lithium-ion battery.
[0027] Detailed Description Throughout this specification, the term "lignin" is intended to refer to any type of lignin that can be used as a carbon source to make carbon materials. Examples of such lignins include, but are not limited to, lignins obtained from plant materials, such as wood (e.g., softwood lignin, hardwood lignin, lignin from annular plants). Lignin may also be chemically modified.
[0028] Preferably, the lignin has been purified or isolated prior to use in the process according to the invention. The lignin may be isolated from the black liquor and optionally further purified prior to use in the process according to the invention. The purification is typically carried out so that the purity of the lignin is at least 90%, preferably at least 95%, more preferably at least 98%, based on the dry weight of the lignin material. Thus, the lignin material used according to the process of the invention preferably contains less than 10%, preferably less than 5%, more preferably less than 2% of impurities (e.g. cellulose, hydrocarbons and inorganic compounds), based on the dry weight of the lignin material.
[0029] Lignin can be obtained by various fractionation methods, for example the organosolv process or the Kraft process. The lignin used in the process of the present invention is preferably Kraft lignin, i.e. lignin obtained by the Kraft process. Kraft lignin is preferably obtained from hardwoods or softwoods, most preferably softwoods.
[0030] The lignin is obtained by the process disclosed in WO2006031175 A1, commonly referred to as the Lignoboost process. This process typically involves precipitating lignin from alkaline black liquor by acidification, separating the precipitated lignin, and reslurrying the lignin at least once under acidic conditions. The resulting lignin can be dried and pulverized to provide solid particles. The lignin obtained by this method typically has a total metal content in the range of 500 ppm to 5000 ppm, the metal content coming mainly from the wood source and from the cooking chemicals added during the pulping process. The pH of the resulting lignin is typically in the range of 3 to 4, and the sulfur content is typically around 1 to 3% by weight.
[0031] Step i) of the method according to the first aspect involves providing a lignin having a total metal content of less than 200 ppm. As used herein, the term "total metal content" refers to the total amount of metals present in the lignin. These metals are typically sodium, potassium, magnesium, calcium, aluminium, iron and manganese. Trace amounts of other metals may also be present. The metal content may be determined by inorganic elemental analysis using inductively coupled plasma optical emission spectroscopy (CP-OES). The total metal content is determined by adding up all the amounts for each metal. The lignin provided in step i) of the method according to the first aspect of the invention has a total metal content of less than 200 ppm, preferably less than 150 ppm, more preferably less than 100 ppm.
[0032] The lignin provided in step i) of the process according to the first aspect may also have an iron content of less than 15 ppm, preferably less than 10 ppm.
[0033] The lignin provided in step i) of the process according to the first aspect may also have a manganese content of less than 10 ppm, preferably less than 6 ppm.
[0034] The lignin provided in step i) of the process according to the first aspect may also have an aluminium content of less than 17 ppm or less than 13 ppm, a calcium content of less than 16 ppm or less than 10 ppm, a potassium content of less than 10 ppm or less than 5 ppm, a magnesium content of less than 42 ppm or less than 25 ppm and a sodium content of less than 30 ppm or less than 15 ppm.
[0035] In an alternative embodiment, the lignin provided in step i) of the process according to the first aspect may have a total metal content in the range of 0 to 200 ppm, such as in the range of 0.1 to 200 ppm, preferably in the range of 0 to 150 ppm, such as in the range of 0.1 to 150 ppm, more preferably in the range of 0 to 100 ppm, such as in the range of 0.1 to 100 ppm.
[0036] In alternative embodiments, the lignin provided in step i) of the method according to the first aspect may have an iron content in the range of 0 to 15 ppm, or in the range of 0 to 10 ppm, or in the range of 0.1 to 15 ppm, or in the range of 0.1 to 10 ppm.
[0037] In alternative embodiments, the lignin provided in step i) of the process according to the first aspect may have a manganese content in the range of 0 to 10 ppm, or in the range of 0 to 6 ppm, or in the range of 0.1 to 10 ppm, or in the range of 0.1 to 6 ppm.
[0038] In an alternative embodiment, the lignin provided in step i) may have an aluminium content in the range of 0-17 ppm or 0-13 ppm, a calcium content in the range of 0-16 ppm or 0-10 ppm, a potassium content in the range of 0-10 ppm or 0-5 ppm, a magnesium content in the range of 0-42 ppm or 0-25 ppm and a sodium content in the range of 0-30 ppm or 0-15 ppm.
[0039] In an alternative embodiment, the lignin provided in step i) may have an aluminium content in the range of 0.1-17 ppm or 0.1-13 ppm, a calcium content in the range of 0.1-16 ppm or 0.1-10 ppm, a potassium content in the range of 0.1-10 ppm or 0.1-5 ppm, a magnesium content in the range of 0.1-42 ppm or 0.1-25 ppm and a sodium content in the range of 0.1-30 ppm or 0.1-15 ppm.
[0040] The lignin provided in step i) of the process according to the first aspect may also have a silicon content of less than 80 ppm, such as in the range of 0 to 80 ppm, or in the range of 0.1 to 80 ppm.
[0041] The lignin provided in step i) of the method according to the first aspect is in solid form, i.e. not in dissolved state. The lignin provided in step i) of the method according to the first aspect is preferably in particulate form, e.g. in powder form. The particle size distribution of the lignin particles is preferably such that at least 80% by weight of the particles have a diameter of less than 0.2 mm. In the context of the present invention, particle diameter is the equivalent spherical diameter of the particle if the particle is not spherical. The equivalent spherical diameter is the diameter of a sphere of equivalent volume.
[0042] The lignin having a total metal content of less than 200 ppm provided in step i) of the process according to the first aspect is preferably obtained by a lignin purification process comprising the following steps: a) providing a solid lignin; b) providing an acidic aqueous solution having a pH below 6; c) soaking the lignin in an acidic aqueous solution for at least 15 minutes, the temperature of the acidic aqueous solution during soaking being in the range of 40° C. to 100° C. to remove metals from the lignin and transfer them to the acidic aqueous solution, thereby obtaining a purified lignin having a total metal content of less than 200 ppm; d) separating the resulting purified lignin from the acidic aqueous solution; and e) Optionally, washing the separated purified lignin Here the lignin remains in solid form during all steps of the process.
[0043] The lignin provided in step a) of the lignin purification process is in solid form, i.e. not in dissolved state. The lignin may be provided in the form of a dry powder. Alternatively, the lignin may be wet or provided in a slurry or suspension. The lignin may also be provided as ground lignin cake obtained from a lignin separation process. The lignin is not dissolved and remains in solid form during any step in the lignin purification process.
[0044] Alternatively, the lignin may be dissolved in small amounts during the steps of the method according to the invention such that only a small fraction of the solid lignin is dissolved, and thus the lignin will remain mostly in solid form, which will be removed during the separation step and discarded from the process.
[0045] The lignin provided in step a) of the lignin purification process may have a total metal content of at least 500 ppm, preferably at least 600 ppm, more preferably at least 700 ppm. In another embodiment, the lignin provided in step a) of the lignin purification process has a total metal content in the range of 500 ppm to 5000 ppm, preferably in the range of 600 ppm to 3000 ppm, more preferably in the range of 700 ppm to 1500 ppm.
[0046] In an alternative embodiment, the lignin provided in step a) of the lignin purification process may have an aluminium content of at least 18 ppm or at least 19 ppm, a calcium content of at least 18 ppm or at least 19 ppm, an iron content of at least 16 ppm or at least 17 ppm, a potassium content of at least 30 ppm or at least 50 ppm, a magnesium content of at least 45 ppm or at least 48 ppm, a manganese content of at least 11 ppm or at least 12 ppm, and a sodium content of at least 400 ppm or at least 650 ppm.
[0047] In an alternative embodiment, the lignin provided in step a) of the lignin purification process may have an aluminium content in the range of 18-25 ppm, preferably in the range of 19-23 ppm, a calcium content in the range of 18-40 ppm, preferably in the range of 19-25 ppm, an iron content in the range of 16-30 ppm, preferably in the range of 17-22 ppm, a potassium content in the range of 30-90 ppm, preferably in the range of 50-70 ppm, a magnesium content in the range of 45-55 ppm, preferably in the range of 48-53 ppm, a manganese content in the range of 11-30 ppm, preferably in the range of 11-16 ppm, and a sodium content in the range of 400-2000 ppm, preferably in the range of 650-1000 ppm.
[0048] Step b) of the lignin purification process involves providing an acidic aqueous solution having a pH below 6. As used herein, the term "acidic aqueous solution" refers to any type of aqueous solution having a pH below 7. The acidic aqueous solution in step b) of the lignin purification process may be provided by adding at least one acid to an aqueous solution. The acidic aqueous solution provided in step b) of the lignin purification process has a pH below 6, preferably below 5, more preferably below 4. In an alternative embodiment, the pH of the acidic aqueous solution may be below 7. In a further alternative embodiment, the pH of the acidic aqueous solution may be in the range of 1-6, preferably in the range of 2-5, more preferably in the range of 1-4.
[0049] Lignin may be added to the aqueous solution after the acid has been added. Alternatively, lignin may be added to the aqueous solution before the acid is added. The aqueous solution is heated either before or after the addition of the acid and lignin. In one embodiment, acid is added to the heated aqueous solution, followed by addition of lignin to the aqueous solution. In another embodiment, lignin is added to the acidic aqueous solution, followed by heating of the aqueous solution. In yet another embodiment, acid is added to the aqueous solution containing lignin. In this embodiment, the aqueous solution is heated either before or after addition of the acid. In a preferred embodiment, lignin is added to the heated aqueous solution, followed by addition of acid to the aqueous solution containing lignin.
[0050] The aqueous acid solution provided in step b) of the lignin purification process comprises at least one acid such that the pH of the aqueous acid solution is below 7, or below 6, or below 5, or below 4. In one preferred embodiment, the aqueous acid solution comprises at least one organic acid. The organic acid may be a carboxylic acid and may be monoprotic, diprotic, or triprotic. In a preferred embodiment, the pKa value of the organic acid is below 4.75 for at least one acid group. The organic acid may be selected from at least one of acetic acid, citric acid, formic acid, and oxalic acid. Preferably, the aqueous acid solution comprises at least one organic acid selected from formic acid and oxalic acid. It has been found that the use of an organic acid further reduces the metal content in the lignin during the steeping step. Organic acids, such as formic acid and oxalic acid, are cheap, easy to handle, have low toxicity, and are usually less restricted by certain waste disposal regulations than acids containing sulfur, nitrogen, and / or phosphorus.
[0051] In an alternative embodiment, the aqueous acid solution comprises at least one inorganic acid, such as sulfuric acid, hydrochloric acid, or phosphoric acid.
[0052] The aqueous acid solution may also include more than one acid, such as a combination of two or more organic or inorganic acids. The aqueous acid solution may also include a combination of an organic acid and an inorganic acid. In one embodiment, the aqueous acid solution includes both formic acid and oxalic acid.
[0053] In one embodiment, the total amount of acid in the aqueous acid solution may be in the range of 0.1-6 wt.%, preferably in the range of 0.5-5 wt.%, based on the total dry weight of lignin added to the aqueous acid solution. As used herein, the term "total amount of acid" refers to the total amount of concentrated acid added to the aqueous acid solution. Increasing the amount of acid can increase the amount of metals removed from the lignin. However, from a process point of view, it is advantageous to avoid using large amounts of acid for cost reasons and to facilitate waste disposal. In addition, increasing the amount of acid in the aqueous acid solution can cause side reactions that can lead to the decomposition of lignin.
[0054] The acidic aqueous solution may further include one or more additives. The additive may be a dispersant, such as glycerol or a fatty acid. The additive may also be an oxidizing agent, such as hydrogen peroxide or EDTA. Other additives include ion exchangers, such as ammonium salts, such as ammonium acetate and ammonium sulfate. The additives in the acidic aqueous solution may enhance the effect of removing metals from lignin.
[0055] Step c) of the lignin purification process involves soaking the lignin particles in an acidic aqueous solution for at least 15 minutes, wherein the temperature of the acidic aqueous solution during soaking is in the range of 40°C to 100°C to remove metals from the lignin and transfer them to the acidic aqueous solution to obtain purified lignin.
[0056] As used herein, the term "soaking" refers to the process of contacting solid lignin (e.g., in the form of lignin particles) with an aqueous acidic solution for a period of time. During the soaking step of the lignin purification process, the entire surface area of the lignin is in contact with the aqueous acidic solution, meaning that the lignin is completely immersed in the aqueous acidic solution.
[0057] The lignin is immersed in the acidic aqueous solution at a temperature in the range of 40°C to 100°C, for example in the range of 50°C to 90°C, or in the range of 60°C to 80°C. In one embodiment, the lignin is immersed in the acidic aqueous solution at a temperature in the range of 40°C to 110°C, for example in the range of 80°C to 100°C. The acidic aqueous solution may be heated by any suitable means known to the skilled person. The temperature is kept in the specified range throughout the immersion process. Heating the acidic aqueous solution increases the metal removal effect. However, using too high a temperature may lead to damage or decomposition of the lignin.
[0058] The soaking time in step c) is at least 15 minutes, preferably at least 30 minutes, or even more preferably at least 1 hour. In alternative embodiments, the soaking time is in the range of 15 minutes to 6 hours, preferably in the range of 30 minutes to 5 hours, or even more preferably in the range of 1 hour to 4 hours. Increasing the soaking time can increase the metal removal efficiency. However, to enable a cost-effective process that can be easily scaled up, it is important that the soaking time is relatively short. However, the soaking time must be long enough to sufficiently remove the metals from the lignin.
[0059] It is preferred that the acidic aqueous solution is agitated during soaking. Any suitable agitation means known to those skilled in the art can be used.
[0060] During the steeping step, the metals are removed from the lignin and transferred to the aqueous acidic solution, thus obtaining a refined lignin. As used herein, the term "refined lignin" refers to a lignin that contains substantially only lignin, for example, at least 99% lignin based on the dry weight of the lignin material, and less than 1% by weight of other components (e.g., cellulose, hydrocarbons, and inorganic compounds) based on the dry weight of the lignin material. In particular, the refined lignin has a reduced amount of metals such that the total metal content is less than 200 ppm, preferably less than 150 ppm, and more preferably less than 100 ppm. As mentioned above, the lignin is not dissolved during the steeping step, which means that the metals are removed from the solid lignin and not from the dissolved lignin. Thus, the refined lignin obtained is also in solid, e.g., particulate, form.
[0061] Step d) of the lignin purification process involves separating the resulting purified lignin, having a total metal content of less than 200 ppm, from the aqueous acidic solution. The purified lignin is in solid form during separation. As used herein, the term "separation" refers to the process of separating the lignin from the aqueous acidic solution.
[0062] In a preferred embodiment, the separation is performed by filtration. Alternatively, the separation can be performed by centrifugation or sedimentation or other suitable means known to the skilled artisan. Since the purified lignin is separated from the aqueous acid solution, the pH of the aqueous acid solution and the lignin during the separation step will be approximately the same as during the soaking step. Thus, the pH of the aqueous acid solution is below 6, preferably below 5, or more preferably below 4 during the step of separating the purified lignin. In one embodiment, the pH of the aqueous acid solution can be in the range of 1-7, preferably in the range of 2-6, more preferably in the range of 2-5, and most preferably in the range of 2-4.
[0063] In one embodiment of the lignin purification method, the soaking and separation steps are repeated at least once. In this embodiment, the separated lignin is soaked in an acidic aqueous solution (for the second time) before the second separation step. The pH and temperature of the acidic aqueous solution and the time of the soaking step are selected as described above. In the embodiment in which the soaking and separation steps are repeated, the parameters (e.g. pH, temperature, and soaking time) can be the same in all the different soaking steps or can vary in the different soaking steps. In one embodiment, the same parameters are used during the two soaking steps. In one embodiment, the pH can be relatively lower in the second soaking step than in the first soaking step. In another embodiment, the soaking time can be relatively shorter in the second soaking time than in the first soaking time. In yet another embodiment, the temperature can be relatively higher in the first soaking step than in the second soaking step. The total soaking time is the sum of the soaking times for each step. Separation is preferably performed by filtration after each soaking step. The metal content of the lignin can be further reduced by adding additional soaking steps and optimizing the parameters (e.g. time, temperature and pH of each step).
[0064] Step e) of the lignin purification process optionally involves washing the separated purified lignin. In one embodiment, the separated purified lignin is washed with an aqueous wash solution. The aqueous wash solution is preferably water. In one embodiment, the separated purified lignin is washed with water until the pH of the water used for washing is neutral.
[0065] The lignin purification process comprises the additional step of drying the separated and optionally washed purified lignin. The thus obtained purified lignin, with a metal content below 200 ppm, is dried after the separation step or after the optional washing step. Drying of the purified lignin can be carried out by methods and equipment known in the art. The temperature during drying is preferably in the range of 60°C to 160°C, more preferably in the range of 100°C to 120°C. Drying can be carried out under reduced pressure or under vacuum. Preferably, the water content of the purified lignin after drying is less than 10% by weight, preferably less than 5% by weight.
[0066] Other inorganic impurities, such as silicon, may also be removed from the lignin and transferred to the aqueous acid solution during the steeping step. Thus, in one embodiment of the method according to the first aspect, silicon is also removed from the lignin and transferred to the aqueous acid solution during the steeping step, and the resulting purified lignin has a silicon content of less than 80 ppm, such as in the range of 0-80 ppm or 0.1-80 ppm.
[0067] The obtained refined lignin may be optionally further processed before the heat treatment. These further processing steps may further include washing and heating steps. One optional processing involves compacting the powdered refined lignin into lignin aggregates, which may be followed by thermal stabilization, thereby obtaining thermally stabilized agglomerated lignin. One method for obtaining such thermally stabilized agglomerated lignin is described in International Publication No. WO20212 / 50604 (WO2021250604 A1).
[0068] Briefly, purified, preferably dried, lignin powder is compacted and the compacted lignin is ground to obtain agglomerated lignin. The compaction of the lignin is preferably carried out by roll compaction. The compaction process produces an intermediate product, in which fine lignin powder is usually fed through a hopper and conveyed by a horizontal or vertical feed screw to a compaction zone, where the material is compacted into flakes by compaction rollers with a defined gap. By controlling the speed of the feed screw and the pressure generation in the compaction zone, flakes with uniform density are obtained. The pressure generation in the compaction zone can preferably be monitored and controlled by the rotation speed of the compaction rolls. As the powder is drawn between the rollers, it enters what is called the nip region, where the density of the material increases and the powder is converted into flakes or ribbons. The rolls used have cavities. The depth of each cavity used in roll compaction is 0.1-10 mm, preferably 1 mm-8 mm, more preferably 1 mm-5 mm, or 1 mm-3 mm. The specific compressive force applied during compaction may vary depending on the equipment used for compaction, but may be in the range of 1 kN / cm to 100 kN / cm. Equipment suitable for carrying out compaction is known in the art.
[0069] In the grinding step, the intermediate product from the compaction step is subjected to grinding or crushing, for example by means of a rotary granulator, a cage mill, a beater mill, a hammer mill or a grinding mill, and / or a combination thereof. During this step, a further intermediate product is generated.
[0070] After grinding, the ground material is preferably subjected to a sieving step to remove fine materials. Additionally, larger materials, e.g., agglomerates greater than 5.0 mm in diameter, can be removed and / or recycled back to the grinding step.
[0071] The agglomerated lignin may also be thermally stabilized by heat treatment. Heating to produce thermally stabilized agglomerated lignin is carried out such that the agglomerated lignin is heated to a temperature in the range of 140-250°C, preferably in the range of 180-230°C. The heating is carried out for at least 1.5 hours, i.e. the residence time of the agglomerated lignin inside the equipment used for heating is at least 1.5 hours. Preferably, heating is carried out for less than 12 hours. Heating can be carried out at the same temperature throughout the heating stage or at different temperatures (e.g. with a temperature stepwise increase or with a temperature gradient). More preferably, heating is carried out such that the agglomerated lignin is first heated to a temperature of 140-175°C for at least 1 hour and subsequently heated to a temperature of 175-250°C for at least 1 hour.
[0072] By undergoing treatments such as agglomeration and heat stabilization, the lignin will be rendered less susceptible to melting / swelling and dimensional changes during subsequent heat treatments.
[0073] In step ii) of the process according to the first aspect of the present invention, lignin having a metal content of less than 200 ppm is subjected to a heat treatment at one or more temperatures in the range of 300°C to 1500°C, wherein the heat treatment is carried out for a total time ranging from 30 minutes to 10 hours to obtain a carbon material.
[0074] As used herein, the term "thermal treatment" refers to a process in which lignin is converted to carbon by heating the lignin at one or more temperatures for a sufficient period of time. Depending on the temperature during the thermal treatment, different types of carbon, such as charcoal or hard carbon, can be obtained from the lignin.
[0075] The heat treatment preferably comprises a pre-heating step, preferably followed by a final heating step. The pre-heating step is preferably carried out at a temperature between 300 and 800°C, for example at a temperature between 500 and 700°C, under an inert atmosphere, preferably under a nitrogen atmosphere. The duration of the pre-heating step is at least 30 minutes, preferably less than 10 hours. The pre-heating and final heating steps can be carried out as separate steps or as one directly following step. The surface area of the product obtained after the pre-heating step is typically between 300 and 700 m, measured by BET with nitrogen gas. 2 / g range.
[0076] The final heating step is preferably carried out at a temperature between 800 and 1500°C under an inert atmosphere, preferably under a nitrogen atmosphere. The duration of the final heating step is at least 30 minutes, preferably less than 10 hours. After the final heating step at 1000°C or higher, the surface area of the resulting product is typically 50 m 2 / g or less.
[0077] The heat treatment is preferably carried out in stages, preferably starting with a pre-heating step at about 300° C., followed by increasing the temperature to about 500° C. The final heating step is preferably carried out at a temperature between 900° C. and 1300° C., for example at about 1000° C.
[0078] Any metals present in the lignin will also remain after conversion to carbon and therefore will be present in the resulting carbon. The weight of the lignin is reduced by conversion to carbon, whereas the weight of any metals present is not affected by the heat treatment to any significant extent. Thus, the total metal content, measured by weight, in the carbon may be increased compared to the total metal content in the lignin from which the carbon was obtained. In one embodiment, the total metal content of the resulting carbon is less than 800 ppm, e.g., less than 600 ppm, or less than 400 ppm, or less than 200 ppm.
[0079] Metals in the carbon can come not only from the lignin starting material, but also from contamination during the process of converting the lignin to carbon.
[0080] In one embodiment, the total metal content of the resulting carbon is in the range of 0 to 800 ppm, such as in the range of 0.1 to 800 ppm, or in the range of 0 to 600 ppm, such as in the range of 0.1 to 600 ppm, or in the range of 0 to 400 ppm, such as in the range of 0.1 to 400 ppm, or in the range of 0 to 200 ppm, such as in the range of 0.1 to 200 ppm.
[0081] In one embodiment, the iron content of the resulting carbon is less than 60 ppm, for example less than 40 ppm, or less than 25 ppm. In one embodiment, the iron content of the resulting carbon is in the range of 0-60 ppm, for example 0-40 ppm, or 0-25 ppm. In one embodiment, the iron content of the resulting carbon is in the range of 0.1-60 ppm, for example 0.1-40 ppm, or 0.1-25 ppm. Carbon with such a low iron content is advantageous for use as an active material in the negative electrode of a secondary battery, because a high iron content would have a negative effect on electrochemical properties, such as long-term cycle performance.
[0082] In one embodiment, the manganese content of the obtained carbon is less than 40 ppm, for example less than 30 ppm, or less than 20 ppm. In one embodiment, the manganese content of the obtained carbon is in the range of 0 to 40 ppm, for example in the range of 0 to 30 ppm, or in the range of 0 to 20 ppm. In one embodiment, the manganese content of the obtained carbon is in the range of 0.1 to 40 ppm, for example in the range of 0.1 to 30 ppm, or in the range of 0.1 to 20 ppm. Carbon with such a low manganese content is advantageous for use as an active material in the negative electrode of a secondary battery, because a high manganese content would have a negative effect on electrochemical properties, such as long-term cycle performance.
[0083] In one embodiment, the resulting carbon has an aluminum content of less than 70 ppm, such as less than 50 ppm, or less than 30 ppm, a calcium content of less than 60 ppm, such as less than 50 ppm, or less than 30 ppm, a potassium content of less than 40 ppm, such as less than 30 ppm, or less than 20 ppm, a magnesium content of less than 170 ppm, such as less than 130 ppm, or less than 90 ppm, and a sodium content of less than 120 ppm, such as less than 90 ppm, or less than 60 ppm.
[0084] In one embodiment, the aluminum content of the resulting carbon is in the range of 0 to 70 ppm, for example, 0 to 50 ppm or 0 to 30 ppm, the calcium content is in the range of 0 to 60 ppm, for example, 0 to 50 ppm or 0 to 30 ppm, the potassium content is in the range of 0 to 40 ppm, for example, 0 to 30 ppm or 0 to 20 ppm, the magnesium content is in the range of 0 to 170 ppm, for example, 0 to 130 ppm or 0 to 90 ppm, and the sodium content is in the range of 0 to 120 ppm, for example, 0 to 90 ppm or 0 to 60 ppm.
[0085] In one embodiment, the aluminum content of the obtained carbon is in the range of 0.1 to 70 ppm, for example, 0.1 to 50 ppm or 0.1 to 30 ppm, the calcium content is in the range of 0.1 to 60 ppm, for example, 0.1 to 50 ppm or 0.1 to 30 ppm, the potassium content is in the range of 0.1 to 40 ppm, for example, 0.1 to 30 ppm or 0.1 to 20 ppm, the magnesium content is in the range of 0.1 to 170 ppm, for example, 0.1 to 130 ppm or 0.1 to 90 ppm, and the sodium content is in the range of 0.1 to 120 ppm, for example, 0.1 to 90 ppm or 0.1 to 60 ppm.
[0086] The silicon content of the resulting carbon is less than 320 ppm, such as less than 240 ppm, or less than 160 ppm.
[0087] The resulting carbon material may be subjected to other processes such as pulverization, classification, coating, and further heat treatment.
[0088] According to a second aspect, the present invention relates to a carbon having a total metal content of less than 800 ppm, such as less than 600 ppm, or less than 400 ppm, or less than 200 ppm. This carbon is obtainable by a method according to the first aspect. The low metal content of the carbon makes it suitable for use in energy storage applications, such as active material in the negative electrodes of secondary batteries. The carbon according to the second aspect may be further defined with reference to the first aspect as specified above.
[0089] According to a third aspect, the present invention relates to a negative electrode for a non-aqueous secondary battery comprising as active material a carbon obtainable by the method according to the first aspect. The carbon according to the third aspect may be further defined with reference to the first aspect as specified above.
[0090] According to a fourth aspect, the present invention relates to the use of a carbon obtainable by the method according to the first aspect as active material in the negative electrode of a secondary battery, such as a lithium-ion battery. The carbon according to the fourth aspect may be further defined with reference to the first aspect as specified above.
[0091] The carbon obtained by the method according to the first aspect is preferably used as an active material in the negative electrode of a non-aqueous secondary battery (e.g., a lithium-ion battery). Prior to use in the negative electrode, the carbon is pulverized to an average particle size of 3-20 μm. When used to manufacture such a negative electrode, any suitable method for forming such a negative electrode can be utilized. In forming the negative electrode, the carbon can be processed with further components. Such further components include, for example, one or more binders for making the carbon into an electrode, a conductive material, such as carbon black, carbon nanotubes, or metal powder, and / or even a Li storage material, such as graphite or lithium. The binder can be selected from, for example, but not limited to, poly(vinylidene fluoride), poly(tetrafluoroethylene), carboxymethyl cellulose, natural butadiene rubber, synthetic butadiene rubber, polyacrylate, polyacrylic acid, alginate, and the like, or combinations thereof. Optionally, a solvent, such as 1-methyl-2-pyrrolidone, 1-ethyl-2-pyrrolidone, water, or acetone, is utilized during processing.
[0092] Working Example The inorganic (e.g. aluminum, calcium, iron, potassium, magnesium, manganese, sodium, and silicon) content in the carbonized samples was evaluated by ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy). Carbon samples were oxidized with hydrogen peroxide and subsequently wet digested with nitric acid in a microwave oven. The inorganic content was quantified by ICP-OES. The total metal content was calculated by combining the individual metal contents.
[0093] Example 1 Kraft lignin powder from the Lignoboost process was added to heated water (60° C.). Oxalic acid (5% by weight based on the dry weight of lignin added to the water) was then added and the mixture was stirred for 4 hours while maintaining the temperature at 60° C. The mixture was then filtered and the lignin was recovered. The above washing process was repeated once more, after which the lignin was recovered and dried at 60° C. to reduce the moisture content to below 5% by weight.
[0094] The washed lignin powder was agglomerated by roller compaction into particles with a size distribution of 0.5-1.5 mm. The agglomerated lignin was slowly heated to 230 °C in a rotary kiln under air for 2 hours to obtain thermally stabilized agglomerated lignin. The thermally stabilized agglomerated lignin was then heated to 500 °C in a rotary kiln under an inert atmosphere for 2 hours to carbonize the lignin and obtain a carbon material.
[0095] The inorganic content was measured for the lignin starting material (sample 0), after washing in acid (sample 1), and after carbonization (sample 2). The results from the ICP analysis are summarized in Table 1. The inorganic content is decreased by the acid washing procedure. The inorganic content is increased comparing samples 1 and 2 due to mass loss as the lignin is converted to carbon.
[0096] TIFF2025511319000001.tif59170
[0097] In light of the above detailed description of the invention, other modifications and variations will be apparent to those skilled in the art. It should be apparent, however, that such other modifications and variations can be made without departing from the spirit and scope of the invention.
Claims
1. 1. A method for producing carbon, comprising the steps of: i) providing lignin having a total metal content of less than 200 ppm; ii) subjecting the lignin to a heat treatment at one or more temperatures in the range of 300° C. to 1500° C., the heat treatment being carried out for a total time of 30 minutes to 10 hours to obtain carbon; A method comprising:
2. 2. The method of claim 1, wherein the lignin provided in step i) has an iron content of less than 15 ppm.
3. 3. The method according to claim 1 or 2, wherein the manganese content of the lignin provided in step i) is less than 10 ppm.
4. 4. The method according to any one of claims 1 to 3, wherein the lignin provided in step i) has an aluminium content of less than 17 ppm, a calcium content of less than 16 ppm, a potassium content of less than 10 ppm, a magnesium content of less than 42 ppm and a sodium content of less than 30 ppm.
5. 5. The method according to claim 1, wherein the lignin provided in step i) is a kraft lignin.
6. 6. The method of claim 1, wherein the lignin is provided in the form of particles, and the particle size distribution of the lignin particles is such that at least 80% by weight of the particles have a diameter of less than 0.2 mm.
7. The lignin provided in step i) is subjected to the following steps: a) providing a solid lignin; b) providing an acidic aqueous solution having a pH below 6; c) soaking the lignin in an acidic aqueous solution for at least 15 minutes, the temperature of the acidic aqueous solution during soaking being in the range of 40°C to 100°C to remove metals from the lignin and transfer them to the acidic aqueous solution, thereby obtaining a purified lignin having a total metal content of less than 200 ppm; d) separating the resulting purified lignin from the acidic aqueous solution; and e) Optionally, washing the separated refined lignin wherein the lignin remains solid during all steps of the process; 7. The method of claim 1 , wherein the composition is prepared by a method comprising:
8. 8. The method of claim 7, wherein the total amount of acid in the acidic aqueous solution is in the range of 0.1 to 6 wt. %, based on the dry weight of the lignin soaked in the acidic aqueous solution.
9. 9. The method of claim 7 or 8, wherein the acidic aqueous solution comprises at least one organic acid.
10. 10. The method of claim 9, wherein the at least one organic acid is selected from formic acid and oxalic acid.
11. 11. The method according to any one of claims 7 to 10, wherein the separation in step d) is carried out by filtration.
12. The method of any one of claims 7 to 11, wherein steps c to d, and optionally e), are repeated at least one time.
13. 13. The method according to any one of claims 7 to 12, wherein the separated lignin is subjected to washing with an aqueous washing solution.
14. 14. The method of any one of claims 7 to 13, comprising the additional step of drying the separated and optionally washed lignin.
15. 15. The method of any one of claims 1 to 14, wherein step ii) comprises a pre-heating step followed by a final heating step.
16. The method according to claim 15, wherein the pre-heating step ii) is carried out at a temperature between 400° C. and 800° C. for at least 30 minutes.
17. 17. The method of claim 15 or 16, wherein the preheating step is carried out in an inert atmosphere.
18. A method according to any one of claims 15 to 17, wherein the final heating step is carried out at a temperature between 800°C and 1500°C for at least 30 minutes.
19. 19. The method of any one of claims 15 to 18, wherein the final heating step is carried out in an inert atmosphere.
20. 20. The process of any one of claims 1 to 19, wherein the total metal content of the resulting carbon is less than 800 ppm.
21. 21. The method of any one of claims 1 to 20, wherein the iron content of the resulting carbon is less than 60 ppm.
22. 22. A process according to any one of claims 1 to 21, wherein the manganese content of the resulting carbon is less than 40 ppm.
23. 23. A process according to any one of the preceding claims, wherein the carbon obtained has an aluminium content of less than 70 ppm, a calcium content of less than 60 ppm, a potassium content of less than 40 ppm, a magnesium content of less than 170 ppm and a sodium content of less than 120 ppm.
24. 1. A carbon derived from lignin, the carbon having a total metal content of less than 800 ppm.
25. 25. The lignin-derived carbon of claim 24, having an iron content of less than 60 ppm.
26. 26. The lignin-derived carbon of claim 24 or 25, having a manganese content of less than 40 ppm.
27. 27. A lignin-derived carbon according to any one of claims 24 to 26 having an aluminium content of less than 70 ppm, a calcium content of less than 60 ppm, a potassium content of less than 40 ppm, a magnesium content of less than 170 ppm and a sodium content of less than 120 ppm.
28. A negative electrode for a non-aqueous secondary battery comprising as active material a carbon obtainable by the method according to any one of claims 1 to 23.
29. 24. Use of the carbon obtainable by the method according to any one of claims 1 to 23 as active material in the negative electrode of a secondary battery.